Development and validation of mathematics courseware usefulness evaluation instrument for teachers - Sahari, Noraidah; Abdul Ghani, Abdul Azim; Selamat, Hasan; Md. Yunus, Aida Suraya (Science Alert, 2009)
The primary purpose of this study was to develop an instrument for evaluating the usefulness of mathematics courseware and to provide psychometric evidence of validity and reliability. Throughout four phases of this study, 696 participants were involved and six types of MCs were used. Each participant was required to evaluate the courseware heuristically and complete the Mathematics Courseware Usefulness Evaluation Instrument (MCUE). Based on the theoretical perspective, a hypothesized model with three factors which were usability, functionality and efficiency, five sub-factors and seven criteria were proposed. This study presents some empirical evidence of whether the evaluation model and its underlying metrics are reliable and valid for determining the usefulness of Mathematics Courseware. A pool of evaluation metrics were collected based on the MC preliminary evaluation survey, related articles on MC reviews and based on several existing evaluation instruments. Through several experiments, we validate an eight-dimension usefulness attribute involving Ease of use, Attractiveness, User control, Concept presentation, reinforcement, assessment, accuracy and learning support material and 56 metrics.